Carbon nanotubes/low density polyethylene composite films for strain sensing - Abdel Chafy, Radwa Raafat (AUC Knowledge Fountain, 2012)
Carbon nanotubes (CNTs) are known to have remarkable mechanical and electrical properties. One of those properties is piezoresistance which makes them suitable to be used in the field of strain sensing. Multi-walled nanotubes (MWNTs) were incorporated in low-density polyethylene (LDPE) matrix to form composite film sensors with different concentrations of 1, 2, 3.5, 5, 6.5, and 8 weight%. The fabrication of such composite was carried out using solid-state mixing, followed by melt blending process. Both extrusion and compression molding processes were used where compression showed more promising results in terms of electrical conductivity. Two types of molds were examined in compression molding, namely flash type mold and a positive type mold. The positive type mold showed better control over process parameters. Furthermore two types of multi-walled carbon nanotubes of different aspect ratios were investigated using the positive type mold to examine their effect on the composite conductivity. The ones with the higher aspect ratio showed much higher conductivity. Strain sensitivity measurements were carried out on composite film samples at percolation threshold and beyond and gauge factors were obtained which showed significantly higher sensitivity than that of conventional strain gauges.